Parental Attitudes Towards Prenatal Genetic Testing For Sickle Cell Disease. Issue 8 (November 2019) - Stevens, Evelyn M.; Patterson, Chavis A.; Tchume-Johnson, Trudy; Antiel, Ryan M.; Flake, Alan; Smith-Whitley, Kim; Barakat, Lamia P.
Abstract : Uptake of prenatal genetic testing (PGT) is low among those with sickle cell disease (SCD). This study evaluated the association of knowledge and attitudes towards prenatal genetic counseling (PGC), awareness of posttesting intervention options and omission bias with attitudes towards PGT. In addition, we explored changes among knowledge, attitudes, and awareness of options following exposure to an educational, clinical vignette among parents of children with SCD. Parents (n=44) completed a questionnaire and an educational, clinical vignette presenting a detailed account of a pregnant woman with sickle cell trait seeking PGT and PGC was read to each participant. t Tests, Spearman correlations, multivariable regressions, and moderation/mediation analyses were used. More positive attitudes towards PGC ( P =0.01), lesser tendency of omission bias ( P <0.01) and private insurance ( P =0.04) were significant correlates of more positive attitudes towards PGT. Omission bias mediated the relationship of attitudes towards PGC and attitudes towards PGT (95% confidence interval: 0.13, 3.03). Awareness of options ( P =0.02), knowledge of PGC ( P =0.01) and knowledge of PGT ( P =0.01) significantly improved after exposure to the clinical vignette. Patients and families with SCD can benefit from education about the importance of prenatal diagnosis to improve attitudes, address omission bias and promote more informed decisions of PGT.